Optimization of Additional Composition Variations ZnO Nanoparticles on The Characteristics of Porous Hydroxypatite as Bone Filler - Azkiyah, Fardatul; Rudyardjo, M.Si., Drs. Djony Izak; Ady, Jan (Indonesian Applied Physics Letters, 2021)
Research on the synthesis and characterization of porous hydroxyapatite with the addition of ZnO nanoparticles has been carried out through a combination of foam immersion and injection methods. This research was conducted to optimize the previous research by increasing the variation of ZnO composition and adding the injection method to the research process. The materials used in this research include hydroxyapatite nanoparticles, ZnO nanoparticles, Aquades, PVA and polyurethane foam. Manufacturing is done by immersing polyurethane foam into a slurry. Slurry is a mixture of PVA and hydroxyapatite solutions with variations in the addition of ZnO nanoparticles (8 wt%, 10 wt%, 12 wt%, and 14 wt%). Then inject the remaining slurry into the foam. After that the sample was dried and heated at a temperature of 650ºC to remove foam and PVA, then the sample was sintered at a temperature of 1200ºC for 3 hours. Based on SEM analysis, porosity test, and compressive strength test, the best results were shown by sample IV because it had a pore diameter of 142.9 – 371.4 m with a porosity of 69.983%, a compressive strength value of 1.8653 MPa and non-toxic. The best results have not met the standard for bone filler application. In further research, improvements need to be made by using other additives such as ZrO2, so that it can improve the mechanical properties of porous hydroxyapatite to meet standard bone filler applications.